(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was carried in the herd of Frieswal crossbred calves. Thirty Frieswal calves (15 male and 15 female) were included in the experiment at 3 days of their birth (after colostrum feeding). They were distributed into 3 groups (3 floor types with 10 calves (5 male + 5 female) in each group): Concrete floor, Concrete floor with straw beddings and Earthen (Kachha) floor. In general, Average daily gain (ADG) showed an increasing trend with the advancement of age. At 9th and 10th week of age i.e., just after stopping of milk feeding ADG decreased however, in subsequent weeks, calves regained their weight gain. From fourth fortnight onward the gains in heart girth were significantly higher (P<0.05) for calves on straw bed and earthen floor than the calves on concrete floor. With advancement of age as expected there was gradual increase in height at withers in all the three groups as the animals were in growing phase. However, the increase in height was comparatively higher for calves on straw bed than the calves on other two floor types. The most striking results of disease incidence were that number of calves under concrete floor which suffered more than once, were 40% whereas calves under earthen floor and straw bed suffering more than once were 20 and 10%, respectively. Occurrence of more than one disease per animal was also more under concrete floor (30%) than under earthen (20%) or straw bed (10%). Thus, calves under concrete floor suffered maximum among the three floor types